The Effect of Gluteus Medius Kinesio Taping on Pain in Athletes with Patellofemoral Pain Syndrome during Functional Tasks - Bagheri 1*, Shahabeddin; Naderi 2, Aynollah; Taherinia 3, Ali; Rezvani 4, Mohammad Hosain (Shahroud Journal of Medical Sciences, 2019)
Background: The weakness of hip muscles, abductors, and external rotators has been confirmed in individuals with patellofemoral pain syndrome in comparison with healthy people. This study investigates the effects of gluteus medius Kinesio taping in athletes with patellofemoral pain syndrome during functional tasks. Methods: A total of 30 females with PFPS were randomly assigned into Kinesio taping group (n = 15) and the placebo group (n = 15). Pain intensity was measured using the numerical pain rating scale in 4 functional tasks; walking, squatting, ascending, and descending stairs, at baseline plus immediately as well as 24 following Kinesio taping. The data were then statistically analyzed. Results: Mixed-model ANOVAs, with repeated measures on time, indicated statistically significant differences between groups in pain over time for walking (P = 0.000), squatting (P = 0.007), and descending stairs tasks (P = 0.000). However, there were no significant differences between groups in the ascending stair task (P = 0.651). Conclusions: The results showed that compared to placebo in reducing pain in athletes with PFPS, gluteus Medius Kinesio taping was effective in functional tasks of walking, squatting, as well ss moving up and down stairs. Keywords: Gluteus medius, Kinesio taping, Patellofemoral pain syndrome, Functional task.